PENINGKATAN HASIL BELAJAR BAHASA INDONESIA MELALUI MODEL PEMBELAJARAN KOOPERAIF TIPE TEAM, GAMES, TOURNAMENT PESERTA DIDIK KELAS X SMA NEGERI 13 MEDAN: Penelitian Tindakan Kelas - Ade Irma; Rika Kartika; Saipul (STKIP Subang, 2025)
This classroom action research aims to improve the learning outcomes of Indonesian language among Grade X-9 students at SMA Negeri 13 Medan through the implementation of the cooperative learning model Team Games Tournament (TGT). The problem addressed was the low academic performance and lack of active participation among students during the learning process. The research was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The instruments used included observation sheets for teacher and student activities, as well as learning outcome tests. The results showed that the implementation of the TGT model significantly improved students' learning outcomes. The percentage of mastery learning increased from 35.29% in the first cycle to 88.23% in the second cycle. Students' learning activities also improved from a moderately active to a highly active category. Therefore, the TGT cooperative learning model proved to be effective in enhancing both students' academic achievement and engagement in Indonesian language learning. This study recommends the use of the TGT model as an engaging and participatory instructional strategy.